2020
DOI: 10.1148/rg.2020190044
|View full text |Cite
|
Sign up to set email alerts
|

Breast Imaging in Transgender Patients: What the Radiologist Should Know

Abstract: Transgender is the umbrella term for individuals whose gender identity and/or gender expression differs from their assigned sex at birth. With the rise in patients undergoing gender-affirming hormone therapy and gender-affirming surgery, it is increasingly important for radiologists to be aware of breast imaging considerations for this population. While diagnostic imaging protocols for transgender individuals are generally similar to those for cisgender women, screening guidelines are more variable. Currently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 54 publications
0
27
0
2
Order By: Relevance
“…Even if diagnostic imaging methods and approaches for transgender individuals are similar to those for cisgender women, screening guidelines are different. Several professional and institutional guidelines have been developed to address breast cancer screening in the transgender population, particularly mammography screening in transfeminine individuals undergoing hormone therapy, as emphasized by Parikh [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…Even if diagnostic imaging methods and approaches for transgender individuals are similar to those for cisgender women, screening guidelines are different. Several professional and institutional guidelines have been developed to address breast cancer screening in the transgender population, particularly mammography screening in transfeminine individuals undergoing hormone therapy, as emphasized by Parikh [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…Transgender women usually will have less lifetime exposure to estrogen and progesterone [21]. Therefore, evidence regarding breast cancer risk in transgender women is conflicting [22].…”
Section: Breast Cancer Screening In Transgender Womenmentioning
confidence: 99%
“…However, Brown and Jones performed a retrospective medical record review of 3566 transgender women, and found that the incidence of breast cancer was similar to that of cisgender women (incidence ratio of [24]. Most recommendations suggest annual or biennial mammographic screening [22]. According to the UCSF Center of Excellence for Transgender Health, "a multidisciplinary program consisting of experts in transgender medicine and surgery at UCSF Medical Center," the risk of breast cancer is thought to be less than or equal to the risk in cisgender women and likely greater than the risk in cisgender males.…”
Section: Breast Cancer Screening In Transgender Womenmentioning
confidence: 99%
See 2 more Smart Citations